New gene markers for classification and quantification of Faecalibacterium spp. in the human gut - Tanno Hiroki; Chatel Jean-Marc; Martin Rebeca; Mariat Denis; Sakamoto Mitsuo; Yamazaki Masao; Salminen Seppo; Gueimonde Miguel; Endo Akihito (OXFORD UNIV PRESS, 2025)
Faecalibacterium prausnitzii is a promising biomarker of a healthy human microbiota. However, previous studies reported the heterogeneity of this species and found the presence of several distinct groups at the species level among F. prausnitzii strains. Our recent study revealed that methods previously developed for quantification of F. prausnitzii were not specific to the species level because of the heterogeneity within the F. prausnitzii species and the application of 16S rRNA gene, which is an invalid genetic marker for the species. Therefore, previously available data failed to provide information on different groups, which limits our understanding of the importance of this organism for host health. Here, we propose an alternative gene marker for quantification of F. prausnitzii-related taxa. A total of nine group-specific primer pairs were designed by targeting rpoA gene sequences. The newly developed rpoA-based qPCR successfully quantified targeted groups. Application of the developed qPCR assay in six healthy adults revealed marked differences in abundance and prevalence among the different targeted groups in stool samples. The developed assay will facilitate detailed understanding of the impact of Faecalibacterium populations at the group level on human health and to understand the links between depletion of specific groups in Faecalibacterium and different human disorders.